Konsep Syura dan Demokrasi dalam Pandangan Al-Qur`an - Novia Permata Sari; Irwan Saputra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article aims to explore the concepts of Shura and Democracy in the Qur'an. The first is to look for comparisons between Shura and Democracy in terms of history and background. This study departs from the debate of Muslim Scholars regarding the relation to the existence of democracy in the Islamic world. So as to produce a mutually beneficial relationship between the two, that Islam and democracy are mutually beneficial and filling. Furthermore, regarding the view that rejects that democracy is incompatible with Islam because it comes from the Western world. Second, attitude in accepting the relationship between Islam and democracy. In this case, Islam has ethical values that underlie the existence of democracy in the Islamic world, which are contained in the principles of al-`ada (Justice), Al-Musawah (Equality) and As-Syura (Deliberation). In the Qur'an there are several verses that can be used as a normative basis. Of these three basic principles of democracy, that democracy does not contradict the Al-Qur'an, in fact the Al-Qur'an provides a moral foundation in building a democratic system